Changes in BODE Quartiles After Pulmonary Rehabilitation Do Not Predict 2-Year Survival in Patients With COPD. Issue 1 (January 2016) - Kavoura, Paraskevi; Kostikas, Konstantinos; Tselebis, Athanasios; Bratis, Dionysios; Kosmas, Epaminondas; Alchanatis, Manos; Koulouris, Nikolaos G.; Bakakos, Petros; Loukides, Stelios
Abstract : PURPOSE: Pulmonary rehabilitation (PR) has well documented positive effects in patients with chronic obstructive pulmonary disease (COPD). The BODE (body mass index, airflow obstruction, dyspnea, and exercise) index reflects the multicomponent nature of COPD. We aimed to determine whether changes in BODE quartiles after a PR program might affect 2-year survival and which characteristics drive changes in BODE quartiles after PR intervention. METHODS: Ninety-five patients with COPD participated in a PR program. The BODE index and anxiety, depression, and quality of life questionnaires were completed before and after the PR program. Five-year survival was recorded for all patients, irrespective of changes in BODE quartiles. RESULTS: Up to 62% of patients with COPD had an improvement in the BODE index, whereas 42% of patients had a change in BODE quartile. Survival did not differ between patients who did not and who did show an improvement in BODE quartiles, despite a trend in favor of the latter (log-rank P = .202). Similar results were observed for patients who did and did not demonstrate a change in the BODE index ≥2 (log-rank P = .679). Significant changes in BODE quartiles were mainly attributed to the duration of the disease, current smoking status, hospitalization rate in the previous year, and the presence of poorer quality of life, as well as to anxiety and depression at baseline. CONCLUSIONS: Pulmonary rehabilitation significantly influenced the BODE index. The significant changes in BODE quartiles were associated with the duration of the disease, current smoking status, increased hospitalization rate, poorer quality of life, anxiety, and depression at baseline, but failed to predict 2-year survival. Abstract : Ninety-five patients with chronic obstructive pulmonary disease participated in pulmonary rehabilitation. Pulmonary rehabilitation significantly influenced the BODE index. Significant changes in BODE quartiles were associated with the duration of the disease, current smoking status, increased hospitalization rate, poorer quality of life, anxiety, and depression at baseline, but failed to predict 2-year survival.